2018
DOI: 10.1039/c7ob02780j
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cathepsin B-sensitive triggers and hydrophilic linkers onin vitroefficacy of novel site-specific antibody–drug conjugates

Abstract: Herein we describe the synthesis and evaluation of four novel HER2-targeting, cathepsin B-sensitive antibody-drug conjugates bearing a monomethylauristatin E (MMAE) cytotoxic payload, constructed via the conjugation of cleavable linkers to trastuzumab using a site-specific bioconjugation methodology. These linkers vary by both cleavable trigger motif and hydrophilicity, containing one of two cathepsin B sensitive dipeptides (Val-Cit and Val-Ala), and engendered with either hydrophilic or hydrophobic character … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…As shown in Figure 1, all tested AFCs had an average FAR of 1.5 calculated from the FAR distribution (Figure 1). As expected, for the same average FAR, the distribution of SGM-based AFCs 7a, 7b, 8a, and 8b was more homogeneous (2 species, FAR 1 and 2) compared to their lysine-conjugated counterparts 9a, 9b, 10a, and 10b (5 or 6 species, ranging from FAR 0 to FAR 5) [16,26,27].…”
Section: Mass Spectrometrysupporting
confidence: 80%
See 1 more Smart Citation
“…As shown in Figure 1, all tested AFCs had an average FAR of 1.5 calculated from the FAR distribution (Figure 1). As expected, for the same average FAR, the distribution of SGM-based AFCs 7a, 7b, 8a, and 8b was more homogeneous (2 species, FAR 1 and 2) compared to their lysine-conjugated counterparts 9a, 9b, 10a, and 10b (5 or 6 species, ranging from FAR 0 to FAR 5) [16,26,27].…”
Section: Mass Spectrometrysupporting
confidence: 80%
“…In this context, our team [16][17][18] and several others [8,19] developed second-generation maleimides or SGM (dibromomaleimide or dithiophenylmaleimide) [16,20] to produce ADCs or AFCs. After mild reduction of the mAb, these SGMs are able to undergo bioconjugation onto mAb through interchain cysteine cross-linking (Scheme 2b) to afford stable AFCs with a controlled FAR.…”
Section: Introductionmentioning
confidence: 99%
“…Bryden et al showed that Val-Ala and Val-Cit dipeptides could be incorporated into NGM linkers. 134 In the first instance, the hydrophobic nature of the Val-Ala motif was reported to cause a significant reduction in reactivity and only the Val-Cit-NGM linker was able to yield 450% of the desired DAR 4 ADC. However, later incorporation of PEG chains off-set the hydrophobicity issue and allowed for the generation of viable ADCs with either dipeptide motif.…”
Section: Disulfide Rebridgingmentioning
confidence: 99%
“…No effect was observed on HER2-negative MCF-7 cells. Although SDCs with a DAR of 1 are not yet as powerful as the corresponding ADCs with a DAR of 4 [79], this work represents the first step towards the design of more efficient small conjugates with higher DARs, opening up the path to further in vivo or even (pre)clinical studies in order to assess their promising potential against solid tumors [80]. Current ADCs targeting HER2 are ineffective in removing cancer cells expressing relatively low HER2 levels of expression.…”
Section: Alternative Adc Formatsmentioning
confidence: 99%